Complements of topologies with short specialization quasiorders - Pierre, Veronica; Richmond, Tom (Topology Proceedings, 2022)
By identifying a topology τ on a finite set X with its specialization quasiorder ≤, we investigate the complements of τ in the lattice of topologies on X in cases where the heights of the specialization posets are small.